Networks in Technology Commercialization. (June 2016) - Mattila, Malla; Lehtimaki, Hanna
This article examines technology commercialization as networked processes. It presents a longitudinal analysis of a technological invention called intelligent paper over a period of 13 years in 1997–2009. In the analysis, six technology commercialization phases are identified and the roles of various actors in each phase are depicted. The study shows how the processes of technology development and commercialization intertwine and shape each other. The study contributes to literature on commercialization of innovation by presenting an empirical case study where the processes of technology development and commercialization are complex and continuously evolving processes.